The Prevalence of Systemic Rheumatic Diseases Among Breast Cancer Patients and Its Relationship With Survival - Veli SUNAR; Öztürk ATEŞ; Alma KORCALI ASLAN; Yusuf KARAKAŞ; Mustafa Kadri ALTUNDAĞ (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the prevalence of systemic rheumatic diseases (SRDs) among patients with breast cancer (BC) and to identify the clinicopathological characteristics of these patients. Patients and methods: A total of 3,744 female patients with BC (mean age 49±11.7 years; range, 18 to 92 years) followed in Hacettepe University Faculty of Medicine, Medical Oncology Department between January 2006 and December 2015 were retrospectively assessed. Patients with or without SRD were compared in terms of clinicopathological features including age, menopausal state, smoking status, Body Mass Index (BMI), age of menarche, age at first labor, and number of children. The groups were also evaluated regarding tumor grade, stage, estrogen receptor and progesterone receptor expression, human epidermal growth factor receptor 2 overexpression, and survival. Results: Of the patients analyzed, 68 (1.81%) had concomitant SRD. Among these patients, 33 (48.6%) had rheumatoid arthritis, eight (11.8%) had familial Mediterranean fever, eight (11.8%) had Behçet’s disease, four (5.8%) had Sjögren’s syndrome, four (5.8%) had systemic lupus erythematosus, six (8.8%) had ankylosing spondylitis, three (4.4%) had systemic sclerosis, one (1.4%) had polymyositis, and one (1.4%) had temporal arteritis. The groups with or without SRDs were similar in terms of age, smoking status, BMI, menopausal state, breast feeding duration, age at menarche and first birth. Stage 1 and 2 BC was more prevalent in SRD patients (74.6% vs. 64.5%, p=0.018). The rate to receive chemotherapy was significantly lower in patients with SRD. However, there was no significant difference in five-year overall survival rates between patients with or without SRD. Conclusion: Among patients with BC, 1.81% had concomitant SRD. These patients were diagnosed at early stages and given chemotherapy less frequently. However, they had similar survival rates compared to those without SRDs.